Dependence of wear intensity on the coating material of the hydraulic cylinder of the garbage truck’s sealing plate - Bereziuk, O.V.; Savulyak, V.I.; Kharzhevskyi, V.O.; Alekseiev, A.Ye. (Problems of Tribology, 2024)
The article is dedicated to the study of the influence of the coating material on the wear rate of the hydraulic cylinder of the mechanism of the garbage truck’s sealing plate. By means of a first-order planning of experiment with first-order interaction effects using the Box-Wilson method, an adequate dependence of the wear rate of the hydraulic cylinder of the mechanism of the garbage truck’s sealing plate on the coating material was determined. It is established that according to the Student’s criterion, among the studied factors of influence, the intensity of wear of the hydraulic cylinder of the mechanism of the garbage truck’s sealing plate is most affected by the iron content in the coating, the least – by the chromium content, and the nickel content affects only indirectly in interaction with the iron content. The response surfaces of the goal function – the intensity of wear of the hydraulic cylinder of the mechanism of the garbage truck’s sealing plate and their two-dimensional sections in the planes of the influence parameters are shown, which allow to clearly illustrate the specified dependence of this goal function on individual influence factors. The expediency of conducting further research to determine ways to further improve the wear resistance of the hydraulic cylinder of the mechanism of the garbage truck’s sealing plate is shown